Animated Teaching of Physical Processes to School children - Ismoilov Azamat Arslanboyevich (Zien Journals, 2022)
New modern technologies and equipment, ie digital measuring instruments, virtual laboratories, animations, electronic textbooks in all subjects, lectures, laboratories and practical classes in the educational process in general secondary schools. , as well as the use of multimedia tools based on them, as well as the effective organization of websites, various scientific-practical, spiritual-enlightenment conferences held at school to increase the effectiveness of education. is becoming increasingly important.
Keywords: physics; physical processes; computer; animation